2011
DOI: 10.1186/ar3304
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental adjuvant arthritis with a novel folate receptor-targeted folic acid-aminopterin conjugate

Abstract: IntroductionFolate receptor (FR)-expressing macrophages have been shown to accumulate at sites of inflammation, where they promote development of inflammatory symptoms. To target such a macrophage population, we designed and evaluated the biologic activity of EC0746, a novel folic acid conjugate of the highly potent antifolate, aminopterin.MethodsUsing a FR-positive subclone of murine macrophage-derived RAW264.7 cells and rat thioglycollate-elicited macrophages, we studied the effect of EC0746 on dihydrofolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 58 publications
(83 reference statements)
2
73
0
Order By: Relevance
“…Of note, many previous studies with other folate-conjugated compounds have shown that their effects are rather specific to FR-expressing diseased tissues without exerting appreciable off-target effects. 22,40 Our findings suggest that, in addition to ADPKD, the targeting of folate-conjugated compounds to kidneys may be a useful approach for numerous other renal epithelial disorders. As long as the high expression level of the FR is maintained in the diseased target cells, it may be possible to achieve specific drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, many previous studies with other folate-conjugated compounds have shown that their effects are rather specific to FR-expressing diseased tissues without exerting appreciable off-target effects. 22,40 Our findings suggest that, in addition to ADPKD, the targeting of folate-conjugated compounds to kidneys may be a useful approach for numerous other renal epithelial disorders. As long as the high expression level of the FR is maintained in the diseased target cells, it may be possible to achieve specific drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The thioglycollate (TG)-elicited macrophages (TG-mac) were harvested from rats intraperitoneally dosed with an aged TG medium. After a 2-h plastic adherence, the respective macrophage populations were ~90% pure based on CD11b/c expression, and ~70% of the CD11b/c cells expressed a functional FR (17).…”
Section: Animals Sources Of Macrophages and Cell Culturementioning
confidence: 99%
“…Rat adjuvant arthritis (AIA) was induced by intradermal inoculation (at the base of the tail) of 0.5 mg heat-killed Mycobacteria butyricum (BD Diagnostic Systems) in 100 μL light mineral oil (Sigma). During the course of disease development, rats were scored three times a week according to the previously established criteria (17). Each paw was graded with a score of 0-4, with a maximum possible score of 16 for each animal.…”
Section: Animals Sources Of Macrophages and Cell Culturementioning
confidence: 99%
See 2 more Smart Citations